Social representations on writing: a systematic review of research articles - Strocchi, María Verónica; Arancibia Gutiérrez, Beatriz; Kloss Medina, Stefanie (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aimed to characterize research on social representations of teachers and students about writing in higher education. The systematic review was carried out following the methodology by the PRISMA Declaration. The search, which was carried out on the Web of Science (WOS), Scopus, Scielo and ERIC databases, identified 20 articles among which the predominating approach was qualitative. The need to explicitly teach writing and the persistence of representations that link writing with assessment and with previous educational levels are recurring elements that stand out.